Risk-shifting, concentration risk, and heterogeneous borrowers - Jens Fittje (International Economics and Economic Policy, 2023)
This article analyzes the effect of endogenous valuations-based capital requirements on risk-shifting in a closed economy DSGE Model. It adds to the existing literature by including concentration risk into the portfolio allocation of the commercial banks. It finds that capital requirements move procyclically, which amplifies the expansionary effect of monetary easing. The movement of the capital requirements is asymmetric, which creates a risk-shifting impulse. Sticky bank capital rents can strengthen this risk-shift.
Keywords: 330; Capital requirements; Risk-shifting; Concentration risk; Monetary policy; DSGE-Model